Proposed synergies between oceanography and metrology - Hartman, Susan E.; Gates, Andrew R.; Lopez-Garcia, Patricia; Bozzano, Roberto; Delory, Eric; Favali, Paolo; Lefevre, Dominique; Chirurgien, Laure; Pensieri, Sara; Petihakis, George; Nair, Rajesh; Neves, Silvana; et al. (Frontiers in Marine Science, 2023)
Accurate and traceable measurements are required to understand ocean processes, to address pressing societal challenges, such as climate change and sustainable management of marine resources. Although scientific and engineering research has resulted in advanced methods to measure Essential Ocean Variables (EOVs) there is a need for cross comparison of the techniques and traceability to recognized standards. Metrological laboratories are experienced in accredited methods and assessment of methodology. An EU INFRAIA-02-2020: Integrating Activities for Starting Communities project MINKE (Metrology for Integrated marine maNagement and Knowledge-transfer nEtwork https://minke.eu) brings European marine science and metrology Research Infrastructures together to identify synergies and create an innovative approach to Quality Assurance of oceanographic data. Quality depends both on the accuracy (that can be provided through the metrology component) and the completeness of the data sets. The collaboration between different Marine Research Infrastructures (RIs) places a fundamental role on assuring the completeness of the datasets, particularly at global scales. The MINKE project encourages enhancement through collaboration of national metrology laboratories and the oceanographic community. Metrological assessment of the accuracy and uncertainties within multidisciplinary ocean observations will provide data that are key to delivering policy information. Objectives across all the RIs are to facilitate ocean observation and build wider synergies. MINKE will investigate these synergies, then introduce metrology to the core of various EOV measurements. Currently the marine RIs cover laboratory to and field operations, from the surface to seafloor, coastal waters to deep sea, fixed ocean stations to ship and autonomous vehicle operations to ships of opportunity ,and flux stations focusing on carbonate system variables. The nexus of these operations is the focal point for coordinated improvement of ocean observing methods. Measurement intercomparisons, traceability and uncertainty assessments should be at the core of the scientific observations. Specifically, MINKE will work with RIs and Metrology Institutes to improve the quality of dissolved oxygen, carbonate system, chlorophyll-fluorescence, ocean sound and current meter measurements, through access to metrology laboratories, Transnational Access and intercomparison studies across existing marine consortia and RIs. MINKE will also promote the development of absolute salinity observation, and improvements in marine litter measurements.